2019
DOI: 10.31629/intek.v3i1.1005
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi, intensitas dan prevalensi endoparasit pada ikan bawal bintang (Trachinotus blochii ) dilokasi budidaya kota tanjungpinang

Abstract: Intensitas parasit merupakan jumlah parasit yang menginvasi organisme pada suatu satuan ruang dan waktu, sedangkan prevalensi parasit merupakan jumlah ikan dalam populasi yang terinvasi parasite. Tujuan dari penelitian ini adalah untuk mengetahui nilai intensitas dan prevalensi akibat invasi endoparasit pada ikan bawal bintang. Metode penelitian di lakukan secara observasi atau pengamatan mikroskopis yang diawali dengan kegiatan isolasi dan di lanjutkan dengan proses identifikasi berdasarkan buku manual id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
5
0
4
Order By: Relevance
“…The high prevalence of endoparasites in the gastrointestinal tract is in line with the high prevalence of parasites in nature [5,6].This is triggered by various factors, such as pollution, imbalance between host and pathogen, and survival of parasitic eggs [7]. Parasite prevalence and intensity categories [3] as in Table 3 and 5 The category of conoidacid oocyst infection was in the moderate category, while the trematode sporocyst infection was in the very severe category. The high intensity value is also influenced by the survival factor of endoparasite eggs and pollution and poor environmental quality.…”
Section: Endoparasites Prevalence and Intensity In Gonggong Conchsmentioning
confidence: 98%
See 1 more Smart Citation
“…The high prevalence of endoparasites in the gastrointestinal tract is in line with the high prevalence of parasites in nature [5,6].This is triggered by various factors, such as pollution, imbalance between host and pathogen, and survival of parasitic eggs [7]. Parasite prevalence and intensity categories [3] as in Table 3 and 5 The category of conoidacid oocyst infection was in the moderate category, while the trematode sporocyst infection was in the very severe category. The high intensity value is also influenced by the survival factor of endoparasite eggs and pollution and poor environmental quality.…”
Section: Endoparasites Prevalence and Intensity In Gonggong Conchsmentioning
confidence: 98%
“…: 1.1 Note: PM / F = Length of male / female; X p M/F = Average length of male/female; X p T = Average total length; Mo = Frequency mode Table 1 shows that the size of the female gonggong conch tends to be longer than the male gonggong conch. The value of the morphometric mode proportion of the gonggong conch's length is 64.60 mm with a sex ratio of 1:1.1 (not ideal) [3] reported that the sex ratio of male and female gonggong conchs in the waters of Madong bay was not balanced since the number of male gonggong conchs tended to be not the same as the number of females gonggong conchs. The unbalanced sex ratio of gonggong conchs is strongly assumed by excessive exploitation pressure [4].…”
Section: Morphometrics and Sex Ratio Of Gonggong Conchs (L Turturella)mentioning
confidence: 99%
“…Tingkat infestasi tungau parasit dapat diukur menggunakan angka prevalensi dan intensitas. Prevalensi merupakan jumlah kucing dalam populasi yang terinfestasi tungau parasit sedangkan intensitas merupakan jumlah tungau parasit yang menginfestasi kucing pada suatu satuan ruang dan waktu (Hakim et al, 2019). Hasil penelitian sebelumnya pada kucing yang diperiksakan di klinik hewan di Ciomas, Kabupaten Bogor, ditemukan ektoparasit yang menginfestasi diantaranya kutu Felicola subrostatus, pinjal Ctenocephalides felis, dan untuk jenis tungau parasit hanya ditemukan Otodectes cynotis dan Sarcoptes scabei.…”
Section: Pendahuluanunclassified
“…terinfestasiAngka prevalensi (Tabel 1) dan intensitas (Tabel 2) kemudian dibandingkan dengan tabel kategori prevalensi dan intensitas menurutHakim et al (2019).…”
unclassified
“…Along with many other nematodes, Camallanus sp. parasites can damage its host digestive tract (Hakim et al, 2019). Aggregation of L3-larvae and L4-larvae, and adult anisakids (including Anisakis sp.)…”
Section: Fish Health Impactsmentioning
confidence: 99%